Allocentric spatial learning and memory deficits in Down syndrome - Lavenex, Pamela Banta; Bostelmann, Mathilde; Brandner, Catherine; Costanzo, Floriana; Fragnière, Emilie; Klencklen, Giuliana; Lavenex, Pierre; Menghini, Deny; Vicari, Stefano (Frontiers in Psychology, 2015)
Studies have shown that persons with Down Syndrome (DS) exhibit relatively poor language capacities, and impaired verbal and visuoperceptual memory, whereas their visuospatial memory capacities appear comparatively spared. Individuals with DS recall better where an object was previously seen than what object was previously seen. However, most of the evidence concerning preserved visuospatial memory comes from tabletop or computerized experiments which are biased towards testing egocentric (viewpoint-dependent) spatial representations. Accordingly, allocentric (viewpoint-independent) spatial learning and memory capacities may not be necessary to perform these tasks. Thus, in order to more fully characterize the spatial capacities of individuals with DS, allocentric processes underlying real-world navigation must also be investigated. We tested 20 participants with DS and 16 mental age-matched, typically developing (TD) children in a real-world, allocentric spatial memory task. During local cue (LC) trials, participants had to locate three rewards marked by local color cues, among 12 locations distributed in a 4 m X 4 m arena. During allocentric spatial (AS) trials, participants had to locate the same three rewards, in absence of local cues, based on their relations to distal environmental cues. All TD participants chose rewarded locations in LC and AS trials at above chance level. In contrast, although all but one of the participants with DS exhibited a preference for the rewarded locations in LC trials, only 50% of participants with DS chose the rewarded locations at above chance level in AS trials. As a group, participants with DS performed worse than TD children on all measures of task performance. These findings demonstrate that individuals with DS are impaired at using an allocentric spatial representation to learn and remember discrete locations in a controlled environment, suggesting persistent and pervasive deficits in hippocampus-dependent memory in DS.